Implementation Of The Independent Curriculum On English Language Learning : Case Study - Setya Ningsih, Azzahra; Ray Dewantara, Aldy; Deswarni, Dini (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
The purpose of this case study was to investigate how the Group Investigation strategy is used in learning English in the classroom, and how it affects learning outcomes, as well as how Merdeka Curriculum is implemented. This study intended to add to the existing literature on the effectiveness of Presentation with Practice as a learning method in the context of comprehension and vocabulary acquisition, particularly in developing students' skills in learning English. Data was collected from interviews, observations, documentation, and report of students in SMAN 03 Mandau and SMKN 02 Pinggir. The results showed that the strategy of Provision of Materials with Practice was effective for teaching English, especially for students' comprehension and vocabulary growth. The use of Projector and Internet as Learning Media, and in the strategy of Presentation with Practice provides an opportunity for students to easily share their views and engage in an effective learning process while working together.